GPCRdb: an information system for G protein-coupled receptors. Issue Volume 44:Issue D1(2016) (17th November 2015) - Isberg, Vignir; Mordalski, Stefan; Munk, Christian; Rataj, Krzysztof; Harpsøe, Kasper; Hauser, Alexander S.; Vroling, Bas; Bojarski, Andrzej J.; Vriend, Gert; Gloriam, David E.
Abstract: Recent developments in G protein-coupled receptor (GPCR) structural biology and pharmacology have greatly enhanced our knowledge of receptor structure-function relations, and have helped improve the scientific foundation for drug design studies. The GPCR database, GPCRdb, serves a dual role in disseminating and enabling new scientific developments by providing reference data, analysis tools and interactive diagrams. This paper highlights new features in the fifth major GPCRdb release: (i) GPCR crystal structure browsing, superposition and display of ligand interactions; (ii) direct deposition by users of point mutations and their effects on ligand binding; (iii) refined snake and helix box residue diagram looks; and (iii) phylogenetic trees with receptor classification colour schemes. Under the hood, the entire GPCRdb front- and back-ends have been re-coded within one infrastructure, ensuring a smooth browsing experience and development. GPCRdb is available at http://www.gpcrdb.org/ and it's open source code at https://bitbucket.org/gpcr/protwis .